2008
DOI: 10.1017/s1751731108002899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish oil on ruminal biohydrogenation of C18 unsaturated fatty acids in steers fed grass or red clover silages

Abstract: Red clover and fish oil (FO) are known to alter ruminal lipid biohydrogenation leading to an increase in the polyunsaturated fatty acid (PUFA) and conjugated linoleic acid (CLA) content of ruminant-derived foods, respectively. The potential to exploit these beneficial effects were examined using eight Hereford 3 Friesian steers fitted with rumen and duodenal cannulae. Treatments consisted of grass silage or red clover silage fed at 90% of ad libitum intake and FO supplementation at 0, 10, 20 or 30 g/kg diet dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
61
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 56 publications
20
61
0
1
Order By: Relevance
“…These results also support the argument for there being a relationship between dietary NDF levels and iso C14:0 and iso C15:0 levels in ruminal microorganisms (Vlaeminck et al, 2006c). A relationship also Lee et al (2008b), and Dewhurst et al (2007), adapted. occurred between linear odd chain fatty acids (OCFA) and the proportion of propionate in the rumen because amylolytic bacteria contains high levels of OCFA (Vlaeminck et al, 2004b(Vlaeminck et al, , 2006c, suggesting that it may be possible to predict rumen fermentation patterns from milk OBCFA, rather than from the chemical composition of the diet. In particular, the lower values of the root mean square prediction error between milk OBCFA and ruminal VFA (3.0%, 9.0% and 8.9% for acetate, propionate and butyrate, respectively), during the validation of the prediction equation (Vlaeminck et al, 2006c), suggest that this new approach is correct.…”
Section: Odd and Branched Chain Fatty Acids: A New Frontier In The Stsupporting
confidence: 82%
“…These results also support the argument for there being a relationship between dietary NDF levels and iso C14:0 and iso C15:0 levels in ruminal microorganisms (Vlaeminck et al, 2006c). A relationship also Lee et al (2008b), and Dewhurst et al (2007), adapted. occurred between linear odd chain fatty acids (OCFA) and the proportion of propionate in the rumen because amylolytic bacteria contains high levels of OCFA (Vlaeminck et al, 2004b(Vlaeminck et al, , 2006c, suggesting that it may be possible to predict rumen fermentation patterns from milk OBCFA, rather than from the chemical composition of the diet. In particular, the lower values of the root mean square prediction error between milk OBCFA and ruminal VFA (3.0%, 9.0% and 8.9% for acetate, propionate and butyrate, respectively), during the validation of the prediction equation (Vlaeminck et al, 2006c), suggest that this new approach is correct.…”
Section: Odd and Branched Chain Fatty Acids: A New Frontier In The Stsupporting
confidence: 82%
“…Nevertheless, recent in vitro and in vivo studies have provided additional insight into possible biochemical pathways accounting for the formation of specific intermediates during the metabolism of LA ( Figure 2) and LNA ( Figure 3). Fish oil or marine algal oil rich in long chain polyunsaturated fatty acids (PUFA) in the diet are known to inhibit the complete biohydrogenation of C18 unsaturated fatty acids resulting in an increase in ruminal trans 18:1 and trans 18:2 outflow Kim et al, 2008;Lee et al, 2008). Incubations with rumen micro-organisms have shown that eicosapentaenoic acid (EPA; cis-5, cis-8, cis-11, cis-14, cis-17 20:5) and docosahexaenoic acid (DHA; Figure 2 Putative pathways describing cis-9, cis-12 18:2 metabolism in the rumen (adapted from Harfoot and Hazlewood, 1988;Hudson et al, 1998;Wallace et al, 2007;Shingfield et al, 2008a).…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
“…Further, higher proportions of C18:1 trans FA and C18:2 cis-9,trans-11, partly deriving from the rumen biohydrogenation intermediate C18:1 trans-11, indicate an inhibition of the terminal biohydrogenation step in cows on ORG farms. An accumulation of biohydrogenation intermediates has been observed by including fish oil in the diet (Lee et al, 2008;Shingfield et al, 2012) or by feeding botanically diverse forages (Lourenço et al, 2008).…”
Section: Effects On Milk Fa Compositionmentioning
confidence: 99%